Simulation of 32-BIT Quadrature Amplitude (QAM) in communication system using MATLAB / Siti Irdayu Tukiman - Tukiman, Siti Irdayu (2003)
This thesis highlights the simulation of communication system by using 32 bit Quadrature Amplitude Modulation (32 QAM) by using Matrix Laboratory (MATLAB) mathematical software. In this study the input and output signal in all block diagrams involves in 32-QAM were analyzed and simulated using simulink toolbox in Matlab software. QAM is adapted since it is still widely used modulation technique eventhough there are various number of new modulation technique evolve today. In modern era, precise and accurate design of any system can be achieved by simulation software, therefore MATLAB version 6.5 is chosen in designing, simulating, testing and analyzing the system. Results show that QAM modulation technique is an efficient modulation technique.